Degradation of the recoverable strain during stress controlled full transformation cycling in NiTi shape memory alloys. (15th March 2019) - Zhang, Yahui; Li, Weichen; Moumni, Ziad; Zhu, Jihong; Zhang, Weihong; Zhong, Sheng-Yi
Abstract: This paper investigates the degradation of the recoverable strain during full transformation cycling in shape memory alloys. Results show that such degradation occurs due to: (i) untransformed austenite during full transformation, (ii) residual martensite after complete unloading, and (iii) plastic strain produced in the latest reverse transformation. Particularly, the plastic strain tends to zero when the stabilized state is reached. Furthermore, the degradation is frequency-dependent in the sense that a higher loading frequency results in a larger degradation of the recoverable strain. Finally, it is shown that fatigue lifetime decreases when transformation degradation increases. Graphical Abstract: